Noncontact triboelectric nanogenerator for human motion monitoring and energy harvesting. (March 2020) - Xi, Yinhu; Hua, Jing; Shi, Yijun
Abstract: Monitoring human motion and harvesting its energy is an interesting and important topic. Triboelectric nanogenerators (TENGs) have shown their potential for signal detecting and energy harvesting. In this paper, a noncontact paper-based TENG is creatively proposed to be used as a self-powered human motion monitoring sensor and also to be used for human motion energy harvesting. The noncontact mode avoids the requirement of direct physical contact between the TENG and the human subject, which fascinates the application of TENG and can increase its service life. It is found that the walking gait cycle (leg raising and falling), moving direction, walking or running speed and moving path can be reflected by the output voltage signals directly and clearly. Noncontact human motion energy harvesting is also achieved by using this TENG with a rectification circuit. It is also surprisingly found that this TENG is able to detect human motion even through a building wall, and the output voltage is strong enough to be captured by a normal multimeter without any additional amplification circuit. This study opens up a new method for self-powered noncontact human movement detecting and monitoring. Graphical abstract: Image 1 Highlights: A self-powered TENG sensor for human motion monitoring is proposed. The TENG is working under noncontact mode. Walking gait cycle, moving direction, speed and path can be detected. Through-wall detection for human motion is achieved.